1988
DOI: 10.1007/bf03350216
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hemiagenesis associated with the right aortic arch

Abstract: The case of a 38-year-old woman with left thyroid hemiagenesis associated with the right aortic arch is presented. The diagnosis of hemiagenesis was established by isotopic and ultrasonic imaging, and also by angiographically defined absence of the left thyroid arteries. The aortogram revealed a right aortic arch with isolation of the left subclavian artery from the aorta. Although the significance and mechanism of the concomitant development of these anomalies is unknown, this case may be the first report in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…No thyroid arteries were seen, but a recurrent laryngeal nerve of typical localization was localized. Similarly, a lack of thyroid arteries was detected on the side of a lobe agenesis in the studies by Mariani et al as well as by Konno and Kanaya [28,30]. This might be a confirmation of a theory of developmental failure of one thyroid lobe due to disturbed vascularization.…”
Section: R R R R Results Esults Esults Esults Esultssupporting
confidence: 58%
See 2 more Smart Citations
“…No thyroid arteries were seen, but a recurrent laryngeal nerve of typical localization was localized. Similarly, a lack of thyroid arteries was detected on the side of a lobe agenesis in the studies by Mariani et al as well as by Konno and Kanaya [28,30]. This might be a confirmation of a theory of developmental failure of one thyroid lobe due to disturbed vascularization.…”
Section: R R R R Results Esults Esults Esults Esultssupporting
confidence: 58%
“…Interestingly, among numerous cases of HT associated with different thyroid pathologies, there were no reports of medullary cancer [20,21]. In a number of patients, HT was accompanied by extrathyroidal abnormalities, including parathyroid adenoma [22], autoimmune polyglandular syndrome type III [23], Williams syndrome [24], pituitary adenoma [25], Down syndrome [26], Marfan syndrome [27], right aortic arch [28] or dysmorphic face with short stature [29]. However, it has never been investigated whether TH is associated with disturbances of the calcium-phosphate balance.…”
Section: R R R R Results Esults Esults Esults Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperthyroidism was reported to be the major reason for diagnosis. In general hypothyroidism was reported in a small group of patients (only in 21 cases) [9,10,13,29,[50][51][52][53]. However Mikosch et al reported a high prevalence of hypothyroidism (7 of 16 patients) in their survey in an iodine deficient geographic area [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism remains an unusual complication of the thyroid hemiagenesis with an uncertain etiology. 10,14,15 Thyroid hormone deficiency is mainly due to peripheral and central nervous system dysfunctions that makes it even more important to diagnose hypothyroidism. 12,16 We conclude that thyroid hemiagenesis and diffuse or focal thyroid disease in the existing thyroid lobe can be demonstrated by ultrasound well and stands as investigation of choice, further associated anomalies are delineated by CT and scintigraphy helps for differentiation between hemiagenesis and suppressed thyroid lobe.…”
Section: Discussionmentioning
confidence: 99%